Hands-on Exercise Manual for LabVIEW Programming, Data Acquisition and Analysis - Beyon, Jeffrey Y. ((Prentice-Hall National Instruments Virtual Instrumentations))
Manual para LabVIEW, programa computacional para uso en laboratorios de investigación científica.